"I could cope so much better if I could just get a good night's sleep" : maternal sleep and mental health from early pregnancy to three years post birth : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Public Health at Massey University, Wellington, New Zealand - Ladyman, Clare Iona (Massey University, 2020)
Healthy sleep is vital to health and wellbeing at all life stages. But for many women, achieving restorative and satisfying sleep consistently throughout pregnancy is challenging. Because vulnerability to experiencing depressive symptoms increases with poor sleep and poor sleep influences the development and trajectory of depressive symptoms, sleep is an important and modifiable factor in the prevention and treatment of depression. Pregnancy is also considered a key teachable life stage as mothers wish to be healthy in order to protect their unborn baby. Yet research investigating non-pharmacological sleep education interventions for preventing perinatal depression is scarce. This thesis comprises three studies that investigate the relationship between maternal sleep health and depression. It presents findings from a scoped review examining sleep health throughout pregnancy; a longitudinal analysis of depression trajectories from late pregnancy to three years post-birth and the association of different sleep dimensions to trajectory group membership; and, the development, implementation and efficacy of a sleep education pilot intervention designed to promote sleep health and reduce the likelihood of depressive symptoms throughout pregnancy. Findings from the scoped review showed that while sleep in pregnancy is highly variable from one woman to the next, significant changes to sleep throughout pregnancy were not indicated for women who were considered physically and mentally healthy. However, the results of the longitudinal analysis revealed that for a sub-group of women, poor sleep was significantly associated with clinically elevated and persistent depressive symptoms throughout the perinatal period and into their child’s preschool years, with the probability of experiencing depressive symptoms especially pronounced for Māori women. The 𝘚𝘭𝘦𝘦𝘱 𝘏𝘈𝘗𝘪 pilot study found recruiting and retaining previously depressed women into a longitudinal perinatal sleep education study achievable and the study design highly acceptable to participants. Similar to the results of the scoped review, self-reported sleep duration, quality, timing, continuity and daytime sleepiness remained stable throughout pregnancy, and at intervention end none of the women in this study were experiencing clinically elevated depressive symptoms. 𝘚𝘭𝘦𝘦𝘱 𝘏𝘈𝘗𝘪 women were compared to a control group from a previous study with no sleep education component; 𝘚𝘭𝘦𝘦𝘱 𝘏𝘈𝘗𝘪 mothers had significantly better sleep initiation and experienced fewer depressive symptoms at intervention completion, though results require confirmation in a larger randomised control group study. Collectively, the findings from these studies highlight the strong relationship between sleep and maternal mental health. Sleep education interventions, such as 𝘚𝘭𝘦𝘦𝘱 𝘏𝘈𝘗𝘪, show promise for minimising depressive symptoms, and optimising sleep for pregnant women. These findings have important health care practice and policy implications and the potential to improve outcomes for mothers, children, families and society.
Keywords: Pregnant women; Mothers; Mental health; Depression in women; Sleep disorders; Treatment; 420313 Mental health services